Activity of N-phenylbenzamide analogs against the neglected disease pathogen, Schistosoma mansoni. (15th February 2023) - Kanyanta, Masebe; Lengwe, Chilufya; Mambwe, Dickson; Francisco, Karol R.; Liu, Lawrence J.; Uli Sun, Yujie; Amarasinghe, Dilini K.; Caffrey, Conor R.; Mubanga Cheuka, Peter
Graphical abstract: Abstract: For the Schistosoma mansoni flatworm pathogen, we report a structure–activity relationship of 25 derivatives of the N -phenylbenzamide compound, 1 (MMV687807 ), a Medicines for Malaria Venture compound for which bioactivity was originally identified in 2018. Synthesized compounds were cross-screened against the HEK 293 mammalian cells. Compounds 9 and 11 were identified as fast-acting schistosomicidal compounds whereby adult worm integrity was severely compromised within 1 h. Against HEK 293 mammalian cells, both compounds exhibited high CC50 values (9.8 ± 1.6 and 11.1 ± 0.2 µM respectively) which could translate to comfortable selectivity. When evaluated in a concentration–response format, compound 9 was active in the nanomolar range (EC50 = 80 nM), translating to a selectivity index of 123 over HEK 293 cells. The data encourage the further investigation of N -phenylbenzamides as antischistosomals.